2005
DOI: 10.1590/s1415-47572005000200014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distance between broodstocks of the marine shrimp Litopenaeus vannamei (Decapoda, Penaeidae) by mtDNA analyses

Abstract: In the constantly growing Brazilian shrimp industry the evaluation of genetic relationships between broodstocks is an useful tool for shrimp culture management programs. We established the genetic relationships between five broodstocks of the white marine shrimp Litopenaeus vannamei (Penaeidae) based on the sequencing of the mtDNA 16S rRNA and cytochrome oxidase I (COI) regions. Although no divergence was found between the broodstocks for the highly conservative 16S rRNA gene, we did find an 8.2% distance betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
6
9
0
2
Order By: Relevance
“…This is particularly important in a situation when no free access to wild populations is available. In Brazil, the reduction in genetic variability and significant differentiation among specific lines has already been reported (Freitas & Galetti Junior, 2002;Francisco & Galetti Junior, 2005;Gonçalves et al, 2005;Magalhães et al, 2007). In the present study, the observed genetic differentiation among hatcheries was reflected by FST values ranging from 0.006 to 0.175 (Table 4).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…This is particularly important in a situation when no free access to wild populations is available. In Brazil, the reduction in genetic variability and significant differentiation among specific lines has already been reported (Freitas & Galetti Junior, 2002;Francisco & Galetti Junior, 2005;Gonçalves et al, 2005;Magalhães et al, 2007). In the present study, the observed genetic differentiation among hatcheries was reflected by FST values ranging from 0.006 to 0.175 (Table 4).…”
Section: Resultssupporting
confidence: 77%
“…One of the immediate concerns of the Brazilian shrimp industry has been the genetic diversity of the available shrimp broodstocks, especially since the country does not have access to wild stocks of L. vannamei. Brazilian L. vannamei broodstocks have multiple origins, with recorded imports from Panama, Ecuador, and Venezuela (Francisco & Galetti Junior, 2005;Gonçalves et al, 2005). However, no detailed information is available about origin, management practices, and performance results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Printed in Brazil www.sbg.org.br 2004) and Litopenaeus setiferus (Ball and Chapman, 2003) but, however, little is known on the genetics of the Brazilian L. vannamei broodstocks Galetti Jr 2002, 2005;De Francisco and Galetti Jr, 2005;Gonçalves et al, 2005). In the work described in the present paper we used microsatellite analysis to investigate the genetic variation in three consecutive generations (F 5 , F 6 and F 7 ) of a Brazilian closed breeder L. vannamei lineage.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CR and 16S rRNA genes have great potential for the inference of genetic diversity and population structure in F. penicillatus. Francisco and Galetti (2005) used mtDNA 16s rRNA and COI regions to evaluate the genetic relationship between five brood stocks of the white marine shrimp Litopenaeus vannamei. Quan et al (2004) also used COI and 16s rRNA genes to examine the phylogenetic relationships between 12 Penaeid shrimp species.…”
Section: Introductionmentioning
confidence: 99%